The senator and the sharecropper : the freedom struggles of James O. Eastland and Fannie Lou Hamer - Asch, Chris Myers (The University of North Carolina Press, 2011)
This is the story of the epic struggle for black equality in the 20th century told through the deeply intertwined life histories of the staunch segregationist and wealthy cotton planter, Senator James O. Eastland, and his sharecropper nemesis, Fannie Lou Hamer, who became the spiritual leader of the civil rights movement.